RETRACTED: The Presence of Acinetobacter baumannii DNA on the Skin of Homeless People and Its Relationship With Body Lice Infestation. Preliminary Results - Ly, Tran Duc Anh; Kerbaj, Jad; Edouard, Sophie; Hoang, Van Thuan; Louni, Meriem; Dao, Thi Loi; Benkouiten, Samir; Badiaga, Sekene; Tissot-Dupont, Herve; Raoult, Didier; Brouqui, Philippe; Mediannikov, Oleg; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
The presence of Acinetobacter baumannii was demonstrated in body lice, however, little is known about the mechanism of natural lice infection. In 2013 and 2014, cross-sectional one-day studies were therefore performed within two Marseille homeless shelters to assess the presence of A. baumannii DNA on human skin, blood and in body lice collected from the same homeless individuals. All 332 participants completed questionnaires, were examined for dermatologic signs, and provided four skin samples (hair, neck, armpits and pelvic belt), blood samples and body lice (if any). We developed a new real-time PCR tool targeting the ompA/motB gene for the detection of A. baumannii for all collected samples. Blood culture was also performed. Body lice were found in 24/325 (7.4%) of subjects. We showed a prevalence of A. baumannii DNA skin-carriage in 33/305 (10.8%) of subjects. No difference was found in A. baumannii DNA prevalence according to body sites. A strong association between body lice infestation (OR=3.07, p=0.029) and A. baumannii DNA skin-carriage was noted. In lice, A. baumannii DNA was detected in 59/219 arthropods (26.9%). All blood cultures and real-time PCR on blood samples were negative for A. baumannii. Lice probably get infected with A. baumannii while biting through the colonized skin and likely transmit the bacteria in their feces. We found no evidence that lice facilitate the invasion of A. baumannii into the blood stream. Further investigations are needed to compare phenotypic and genotypic features of A. baumannii isolates from human skin and lice from the same individuals.